PERAN KUA DALAM PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA (KDRT) MELALUI PROGRAM BIMBINGAN PERKAWINAN DI KECAMATAN TAMANSARI - Putri Sakina; Fatimah Azzakia; Risa Imelia Sintia (STKIP Subang, 2026)
Domestic Violence (DV) remains a serious social issue in Indonesia, with most cases occurring within households and marital relationships. As the institution responsible for marriage affairs, the Office of Religious Affairs (Kantor Urusan Agama/KUA) plays a strategic role in preventing domestic violence through the Premarital Guidance Program (Bimbingan Perkawinan/Bimwin) for prospective brides and grooms. This study aims to describe the implementation of the Premarital Guidance Program at the KUA of Taman Sari District and to analyze its role in preventing domestic violence. This research employed a descriptive qualitative approach. Primary data were obtained through interviews with Bimwin officers, while secondary data were collected from laws and regulations, books, and scientific journals. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the Premarital Guidance Program at the KUA of Taman Sari District has been implemented in accordance with the applicable regulations and serves as a preventive effort against domestic violence by equipping prospective couples with healthy communication skills, conflict resolution strategies, and an understanding of the rights and obligations of spouses. Post-marital conflicts are addressed through mediation by BP4, while domestic violence cases are referred to formal legal procedures. However, the program continues to face challenges due to limited funding and time allocation. Therefore, greater budgetary support and post-marital guidance are recommended to enhance the program's effectiveness in preventing domestic violence.